2017
DOI: 10.1039/c7nr06719d
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport in gel and gel–liquid systems for LiClO4-doped PMMA at the meso- and nanoscales

Abstract: Solid and gel electrolytes offer significant advantages for cycle stability and longevity in energy storage technologies. These advantages come with trade-offs such as reduced conductivity and ion mobility, which can impact power density in storage devices even at the nanoscale. Here we propose experiments aimed at exploring the ion transport properties of a hybrid electrolyte system of liquid and gel electrolytes with meso and nanoscale components. We focus on single pore systems featuring LiClO-propylene car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…43 The switch of surface charge polarity from negative in water to positive in propylene carbonate was agnostic to the pore material and occurred in pores prepared in PET, polycarbonate, and even glass pipettes. 43,55 Previous experiments were performed with conically shaped nanopores, which in symmetric electrolyte conditions rectify ion current such that the I−V curve asymmetry informs on the polarity of surface charges. With the ground electrode placed at the narrow side of the cone-shaped pores, a negatively charged nanopore in aqueous solutions rectified the current such that negative currents were higher than positive currents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43 The switch of surface charge polarity from negative in water to positive in propylene carbonate was agnostic to the pore material and occurred in pores prepared in PET, polycarbonate, and even glass pipettes. 43,55 Previous experiments were performed with conically shaped nanopores, which in symmetric electrolyte conditions rectify ion current such that the I−V curve asymmetry informs on the polarity of surface charges. With the ground electrode placed at the narrow side of the cone-shaped pores, a negatively charged nanopore in aqueous solutions rectified the current such that negative currents were higher than positive currents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…I on transport and associated ionic equilibria feature prominently in a variety of condensed phase phenomena from energy storage in batteries 1 and colloidal stability 2 in materials science to plant growth 3 and nerve signal propagation in biology. 4 A large number of these phenomena involves ions traveling through and interacting in confined spaces that typically reach nanoscale dimensions.…”
mentioning
confidence: 99%
“…The literature also contains various gel-assisted techniques for enhancing the ion transport in conical- and cylindrical-shaped nanopores (see gel-assisted ion transport in Figure ). ,,, Lin et al used high-molecular-weight poly l -lysine to fill conical mesopores with a tip diameter of around 400 nm and found that the addition of the gel significantly improved the ion selectivity of the nanopores compared to that of bare nanopores as a result of an ICP effect near the tip of the nanopore. ,, Yeh et al showed that the maximum power generation of a nanopore filled with poly­(vinyl alcohol) (PVA) gel electrolyte was around 100% higher than that of an aqueous nanopore since the gel lowered the internal membrane resistance through a negative surface charge polyelectrolyte-like increase in the space-charge-governed phenomenon.…”
Section: Enhancing Ion Transport In 1d-nanoporesmentioning
confidence: 99%
“…143,144,150,151 Lin et al 143 used high-molecular-weight poly L-lysine to fill conical mesopores with a tip diameter of around 400 nm and found that the addition of the gel significantly improved the ion selectivity of the nanopores compared to that of bare nanopores as a result of an ICP effect near the tip of the nanopore. 143,152,153 Yeh et al 150 showed that the maximum power generation of a nanopore filled with poly(vinyl alcohol) (PVA) gel electrolyte was around 100% higher than that of an aqueous nanopore since the gel lowered the internal membrane resistance through a negative surface charge polyelectrolyte-like increase in the space-charge-governed phenomenon. Various techniques have been employed for the fabrication of multipore membranes, including reactive ion etching, plasma etching, track etching, and so on.…”
Section: Enhancing Ion Transport In 1d-nanoporesmentioning
confidence: 99%